A Performing Rights Organization Perspective: The Challenges of Enforcement in the Digital Environment - McGivern, Joan M. (The Columbia Journal of Law & the Arts, 2011)
This Article focuses on some of the practical challenges that the American Society of Composers, Authors and Publishers (“ASCAP”) faces in its day to day business efforts to license the public performing right in copyrighted musical works in the digital age under its antitrust consent decree. In looking to the practical, this Article affirmatively does not delve into the development and use of the United States’ antitrust laws in setting fees for the public performance of the music in ASCAP’s repertory. In addition, the author notes that the comments made herein are necessarily constrained by having to navigate between the Scylla and Charybdis of ASCAP’s many pending court proceedings, negotiations and restrictions of protective orders. Nonetheless, while being mindful of these limitations, there is still much to say, from a practical perspective, beginning with: what does it mean to apply for an ASCAP license under ASCAP’s consent decree?